Cross‐protection between antigenically distinct H1N1 swine influenza viruses from Europe and North America - De Vleeschauwer, Annebel R. (Influenza Other Respir Viruses, 2010)
Please cite this paper as: De Vleeschauwer et al. (2011) Cross‐protection between antigenically distinct H1N1 swine influenza viruses from Europe and North America. Influenza and Other Respiratory Viruses 5(2), 115–122. Background  An avian‐like H1N1 swine influenza virus (SIV) is enzootic in swine populations of Western Europe. The virus is antigenically distinct from H1N1 SIVs in North America that have a classical swine virus‐lineage H1 hemagglutinin, as does the pandemic (H1N1) 2009 virus. However, the significance of this antigenic difference for cross‐protection among pigs remains unknown. Objectives  We examined protection against infection with a North American triple reassortant H1N1 SIV [A/swine/Iowa/H04YS2/04 (sw/IA/04)] in pigs infected with a European avian‐like SIV [A/swine/Belgium/1/98 (sw/B/98)] 4 weeks earlier. We also examined the genetic relationships and serologic cross‐reactivity between both SIVs and with a pandemic (H1N1) 2009 virus [A/California/04/09 (Calif/09)]. Results  After intranasal inoculation with sw/IA/04, all previously uninfected control pigs showed nasal virus excretion, high virus titers in the entire respiratory tract at 4 days post‐challenge (DPCh) and macroscopic lung lesions. Most pigs previously infected with sw/B/98 tested negative for sw/IA/04 in nasal swabs and respiratory tissues, and none had lung lesions. At challenge, these pigs had low levels of cross‐reactive virus neutralizing and neuraminidase inhibiting (NI) antibodies to sw/IA/04, but no hemagglutination‐inhibiting antibodies. They showed similar antibody profiles when tested against Calif/09, but NI antibody titers were higher against Calif/09 than sw/IA/04, reflecting the higher genetic homology of the sw/B/98 neuraminidase with Calif/09. Conclusions  Our data indicate that immunity induced by infection with European avian‐like H1N1 SIV affords protection for pigs against North American H1N1 SIVs with a classical H1, and they suggest cross‐protection against the pandemic (H1N1) 2009 virus.